2019
DOI: 10.1108/intr-02-2019-0044
|View full text |Cite
|
Sign up to set email alerts
|

The Government of Jamaica’s electronic procurement system: experiences and lessons learned

Abstract: Purpose Realizing value from information and communication technology (ICT) in procurement in developing countries is complex due to diverse stakeholders and intertwined procurement processes. The purpose of this paper is to examine the experience of the Government of Jamaica in leveraging ICTs as an intervention to transform its procurement operations and combat corruption. Design/methodology/approach The study examines conversations with employees in the Government of Jamaica to understand key milestones i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 54 publications
1
18
0
1
Order By: Relevance
“…In relation to the research question and literature review, this section discusses the findings of the study. While stakeholder viewpoints are relevant for the effective understanding of e-procurement platform implementation [2], this study suggests that their responses to such initiatives sometimes run contrary to the viewpoints. It is evident from the case analysis that though some stakeholders are pleased with the eprocurement platform implementation because of the realization of some viewpoints, there is still skepticism about the success of the project.…”
Section: Discussionmentioning
confidence: 73%
“…In relation to the research question and literature review, this section discusses the findings of the study. While stakeholder viewpoints are relevant for the effective understanding of e-procurement platform implementation [2], this study suggests that their responses to such initiatives sometimes run contrary to the viewpoints. It is evident from the case analysis that though some stakeholders are pleased with the eprocurement platform implementation because of the realization of some viewpoints, there is still skepticism about the success of the project.…”
Section: Discussionmentioning
confidence: 73%
“…Therefore, the satisfaction dimension used in the e-procurement literature is related to the system's ease of use and usefulness (criteria) that can influence user satisfaction. Ahmad et al (2019) discussed trust issues in e-procurement where the users were able to gain their trust and engage with the system processes if the system had the transparency element. Other than that, ease of use of the system can be associated with the satisfaction dimension, in which using the e-procurement system effortlessly (Ramkumar et al, 2019) influences users to use the system (Ibem et al, 2020).…”
Section: Figurementioning
confidence: 99%
“…In addition, some studies [11,18] have argued that e-government cannot eliminate public sector corruption. However, numerous studies [3,5,13,30] have suggested that e-government technologies and apps can reduce corruption in the public sector by addressing problems such as lack of accountability, ineffective governance, information inequalities, and service delays between others. On the other hand, some studies contend that e-government may not be sufficient to address corrupt behaviours that have remained even after the digitization of public services [31].…”
Section: Literature Reviewmentioning
confidence: 99%
“…e-government is the use of ICTas a tool to provide services to the citizens, businesses, and government institutions e ectively and e ciently. us, enable government to be more e ective and trustworthy and sharply increase the possibilities of establishing and mitigating corruption [1][2][3][4]. Many countries across the globe are experiencing high levels of corruption, particularly in developing countries.…”
Section: Introductionmentioning
confidence: 99%